Method for manufacturing recycled polyamide

JP2025010552APending Publication Date: 2025-01-22ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023032202
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-03-02
Publication Date
2025-01-22

AI Technical Summary

Benefits of technology

【0014】 本発明によれば、ウレタン被覆されたポリアミド基布から効率よく高収率でポリアミド基布を製造する方法を提供できる。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a method for efficiently manufacturing regenerated polyamide in a high yield from an urethane-coated polyamide base fabric.SOLUTION: There is provided a manufacturing method for recycled polyamide, which is a manufacturing method for recycled polyamide using a mixture containing a polyamide coated with an urethane resin as a raw material, comprising a dissolving step of dissolving the polyamide by mixing the mixture with a metal chloride alcohol solution containing a metal chloride and an alcohol to obtain a polyamide solution. In the dissolving step, a mass ratio of the polyamide in the polyamide solution is 5 to 15 mass%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing recycled polyamide. More specifically, the present invention relates to a method for producing recycled polyamide using a polyamide base fabric coated with urethane as a raw material. [Background technology]

[0002] Polyamides, including nylon 6 and nylon 66, which are representative engineering plastics, have heat resistance and good mechanical properties and are widely used in textiles, automobile parts, electrical appliance parts, etc., and are one of the materials that cannot be replaced in modern society. Among them, nylon 66 is particularly important because it is used in applications that require heat resistance and durability in harsh environments.

[0003] In recent years, technological developments have been made regarding the recycling of plastics with the aim of saving resources and achieving carbon neutrality, and polyamide is no exception.

[0004] Recycling can be broadly divided into material recycling, which re-pelletizes molded products, and chemical recycling, which reuses monomers through depolymerization. Material recycling raises concerns that the quality of the product may not be stable because the deterioration of the polymers and additives contained in the molded products remain in the recycled polymer. However, material recycling is chosen when recycling is intended for a fixed purpose, since it does not involve chemical reactions and requires fewer auxiliary materials, and therefore requires fewer resources and energy. In addition, before chemical recycling, when additives and coatings are removed from processed and used polyamides collected from factories and markets, a process of recovering clean polyamide is carried out in the same way as in material recycling, so material recycling technology is also useful for chemical recycling. As mentioned above, processed and used polyamides contain various impurities, so the recovery method needs to be changed depending on the application. Polyamides have a wide range of applications, but one of the applications of nylon 66 is in automobiles, where high safety is required. For example, it is used in engine parts that require high heat resistance, and in airbag base fabrics that require durability in the event of a rupture. Among them, airbag base fabrics are least susceptible to deterioration and are suitable for material recycling. Not only used airbags, but also scraps generated when cutting out parts during the manufacture and sewing of airbag base fabrics can be recycled. Generally, airbag fabrics are made by spinning nylon 66, weaving it into a woven fabric, and then coating it with resin. Therefore, in order to recycle airbag fabrics, it is necessary to separate this coating from the nylon 66. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 5841598 [Patent Document 2] Patent No. 7024037 [Patent Document 3] JP 2018-172618 A [Patent Document 4] Patent No. 5110704 Summary of the Invention [Problem to be solved by the invention]

[0006] Physical methods for removing impurities from polyamide containing impurities to produce a clean state include a method in which the recovered material is crushed and then separated by specific gravity (Patent Document 1). Although this method requires little energy to separate the impurities, it is difficult to separate the impurities from the polyamide in the case of airbag base fabrics, in which the polyamide and the impurities are strongly bound together by mixing, bonding, adhesion, etc.

[0007] There is also a method of dissolving and removing impurities such as unnecessary coating resins in part or in whole using a solvent (for example, Patent Document 2). However, since the coating resin is in a state of permeating the polyamide fibers, the coating resin remains in the recovered polyamide. In addition, the recovered polyamide is recovered in the form of crushed cloth. Used airbags and scraps from manufacturing have various shapes, and it is difficult to reuse them as they are, or in the form of fiber waste obtained by cutting them. In addition, even if they are melted and reused, they are not suitable for feeding into an extruder or the like.

[0008] Conversely to the above-mentioned method, it is also possible to dissolve the polyamide in a solvent once, remove impurities as insoluble matter, and then precipitate and recover the polyamide by some method. However, many of the solvents for dissolving polyamide are not suitable for industrial use, such as strong acids such as formic acid and sulfuric acid, and expensive solvents such as HFIP. An example of the use of a solvent that is easy to use industrially is a dissolution and recovery method using ethylene glycol (Patent Document 3). However, this method requires a very high-temperature reaction, which raises concerns about glycolysis of the polyamide, and it is also necessary to distill and dry the used solvent from the sherbet-like solid, which is thought to require a lot of energy in addition to the heating required during the reaction.

[0009] Therefore, there is also a method of dissolving using an alcoholic calcium chloride solution, which is a low-temperature method using a general-purpose raw material. For example, Patent Document 4 describes a method in which a polyamide cloth coated with a coating resin is treated with a methanol solution of calcium chloride to dissolve the polyamide, and the polyamide is diluted with a large amount of water or methanol to obtain the target polyamide as a powder. However, problems became apparent when actually dissolving a resin-coated polyamide base fabric using the method described in Patent Document 4. Patent Document 4 describes that it is preferable to use calcium chloride dihydrate, which has high solubility for polyamide, or to add an amount of water equivalent to the hydrate in addition to calcium chloride anhydride, because the solubility of polyamide in this composition is high.

[0010] However, when actually attempting to dissolve polyamide fabric, a problem became apparent. The problem was the low recovery rate. Even if attempting to dissolve polyamide at about 23%, which is the saturated solubility in the solvent composition, if the fabric had a certain area, it was not possible to dissolve and recover all of the polyamide due to the fabric sticking to itself or wrapping around itself. The dissolved supernatant was also cloudy and in a fluid state, but it was difficult to say that the polyamide was dissolved. One method to increase the yield is to crush the fabric in advance, but in that case, tiny pieces of the coating resin were dispersed in the liquid, making it very difficult to recover it from the solution.

[0011] An object of the present invention is to provide a method for efficiently producing regenerated polyamide in high yield from a urethane-coated polyamide base fabric. [Means for solving the problem]

[0012] After extensive research into a method for recovering polyamide using a methanol solution of calcium chloride, the researchers discovered that the cause of the decrease in recovery efficiency is the increase in viscosity caused by the dissolution of polyamide. As a result, they found that processing with a composition with the highest solubility is not necessarily a liquid composition that will recover polyamide (e.g., nylon 66) in high yield. After further research into the dissolving composition, they found metal chlorides other than calcium chloride that can be used, and also found that the yield of regenerated polyamide can be increased by controlling the polyamide or solution viscosity of the polyamide solution after dissolution, which led to the completion of the invention.

[0013] That is, the present invention is as follows. [1] A method for producing recycled polyamide using a mixture containing a polyamide coated with a urethane resin as a raw material, comprising: a dissolving step of dissolving the polyamide by mixing the mixture with a metal chloride alcohol solution containing a metal chloride and an alcohol to obtain a polyamide solution, In the dissolving step, the mass ratio of the polyamide in the polyamide solution is 5 to 15 mass%. A method for producing recycled polyamide. [2] A method for producing recycled polyamide using a mixture containing a polyamide coated with a urethane resin as a raw material, comprising: a dissolving step of dissolving the polyamide by mixing the mixture with a metal chloride alcohol solution containing a metal chloride and an alcohol to obtain a polyamide solution, In the dissolving step, the viscosity of the polyamide solution at 25°C is 10 to 20,000 mPa s. A method for producing recycled polyamide. [3] The method according to [1] or [2], wherein in the dissolving step, the mixture and the alcohol solution of the metal chloride are mixed at a temperature of 30 to 90° C. [4] The method according to any one of [1] to [3], wherein the polyamide is an aliphatic polyamide. [5] The method according to any one of [1] to [4], wherein the metal chloride is zinc chloride or calcium chloride. [6] The method according to [5], wherein the metal chloride is calcium chloride. [7] The method according to any one of [1] to [6], wherein the alcohol is methanol. [8] The method according to any one of [1] to [7], wherein the polyamide is nylon 66. [9] The method according to any one of [1] to [8], wherein the metal chloride alcohol solution is a solution produced by separating polyamide from a metal chloride alcohol solution in which polyamide has been dissolved from a polyamide base fabric.

[10] The method according to [9], wherein the metal chloride alcohol solution is a concentrated solution obtained after separating polyamide. Effect of the Invention

[0014] According to the present invention, a method for producing a polyamide base fabric from a urethane-coated polyamide base fabric efficiently and in high yield can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, an embodiment of the present invention (hereinafter simply referred to as "the present embodiment") will be described in detail.

[0016] The method for producing recycled polyamide in this embodiment is a method for producing recycled polyamide using a mixture containing polyamide coated with a urethane resin as a raw material, and includes a dissolving step of mixing the mixture with a metal chloride alcohol solution containing a metal chloride and alcohol to dissolve the polyamide to obtain a polyamide solution, and in the dissolving step, the mass proportion of polyamide in the polyamide solution is 5 to 15 mass%. Another embodiment of the method for producing recycled polyamide is a method for producing recycled polyamide using a mixture containing polyamide coated with a urethane resin as a raw material, and includes a dissolving step of mixing the mixture with a metal chloride alcohol solution containing a metal chloride and alcohol to dissolve the polyamide to obtain a polyamide solution, and in the dissolving step, the viscosity of the polyamide solution at 25°C is 10 to 20,000 mPa s. The manufacturing method of this embodiment may be, for example, a method for manufacturing regenerated polyamide, which includes a step of dissolving and extracting polyamide from a urethane-coated polyamide base fabric using an alcoholic solution of a metal chloride having a controlled water content.

[0017] The compounds and the like used in the production method of this embodiment will be described.

[0018] <Mixture> (polyamide) As the polyamide, a polymer polymerized through an amide bond, such as a polycondensation product of a diamine compound and a dicarboxylic acid compound, or a ring-opening polymerization product of a cyclic lactam, can be used. The diamine compound is not particularly limited, but examples thereof include ethylenediamine, trimethylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, nonanediamine, methylpentanediamine, and p-phenylenediamine. The dicarboxylic acid compound is not particularly limited, but examples thereof include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, terephthalic acid, and isophthalic acid. The cyclic lactam is not particularly limited, but examples thereof include ε-caprolactam, undecane lactam, and lauryllactam. The combination of the diamine compound, the dicarboxylic acid compound, and the cyclic lactam compound is not particularly limited, and a plurality of types of each compound may be used in combination. Polyhexamethylene adipamide (nylon 66) (for example, polyhexamethylene adipamide made of hexamethylene diamine and adipic acid) has high solubility and is suitable for the method for producing polyamide of this embodiment.

[0019] The mixture contains a polyamide coated with a urethane resin. The mixture may be composed only of a polyamide coated with a urethane resin, or may further contain other components. In particular, from the viewpoint of the production efficiency of the recycled polyamide, the mass proportion of the polyamide coated with the urethane resin is preferably 30 to 100 mass% relative to 100 mass% of the mixture, more preferably 60 mass% or more, even more preferably 70 mass% or more, and particularly preferably 80 mass% or more.

[0020] The polyurethane resin is obtained by reacting a polyol component with a polyisocyanate component. Examples of the polyol component include polycarbonate polyol, polyester polyol, and polyether polyol. The urethane resin is not particularly limited, but examples thereof include polyester-based polyurethane resins, polyether-based polyurethane resins, polycarbonate-based polyurethane resins, etc. The urethane resin may contain a crosslinking agent such as epoxy, melamine, or polyfunctional isocyanate, a carbodiimide-based hydrolysis inhibitor, a phenol, an aromatic amine antioxidant, an ultraviolet absorber such as a salicylic acid-based, benzophenone-based, or benzotriazole-based derivative, or a flame retardant such as thiourea.

[0021] The polyamide coated with urethane resin may be coated with other coatings in addition to the urethane resin. The type of other coating is not particularly limited, but examples include polyethylene, polypropylene, polyester, and fluororesin. It is preferable that the coating resin is not dissolved in the metal chloride alcohol solution used for dissolution. It is preferable that the coating resin does not contain silicone resin. The polyamide coated with urethane resin may be a recycled polyamide raw material, for example, process waste or waste from molded products such as fibers, automobile parts, and electrical appliance parts using polyamide as a raw material.Specific examples include process waste or waste from clothing, airbags, tire cords, engine compartments, intake systems, fuel system parts, connectors, fishing nets, UD tapes, etc.

[0022] The mixture may contain sewing thread. The material of the sewing thread is not particularly limited, but it is preferably the same polyamide as the base fabric, since it can be recovered as recycled polyamide.

[0023] <Metal Chloride Alcohol Solution> As a solvent for dissolving polyamide, an alcohol solution of a metal chloride is used. The metal chloride alcohol solution contains a metal chloride and an alcohol, and may further contain other components. In particular, the total mass ratio of the metal chloride and the alcohol to 100% by mass of the metal chloride alcohol solution is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 100% by mass.

[0024] The metal chloride is not particularly limited, but examples thereof include zinc chloride, magnesium chloride, calcium chloride, etc., with zinc chloride and calcium chloride being preferred, and calcium chloride being most preferred. The metal chloride used as the raw material may be either anhydrous or hydrated.

[0025] The mass ratio of the metal chloride to the alcohol solution of the metal chloride (100 mass%) is preferably 10 to 25 mass%. If it is less than 10 mass%, the amount of polyamide dissolved is small, and a large amount of solvent is required. If it exceeds 25 mass%, the metal chloride is likely to remain undissolved and is likely to be mixed in as an impurity.

[0026] The amount of water in the alcohol solution of the metal chloride is not particularly limited, but it is preferable that the amount of water is 4 moles or less per mole of metal chloride in the solution.

[0027] Examples of the alcohol include methanol, ethanol, n-propanol, 2-propanol, etc. Among them, methanol is preferred from the viewpoint of the solubility of polyamide.

[0028] The method for mixing the metal chloride and the alcohol is not particularly limited, but if it is a batch type, stirring is preferable. Calcium chloride will dissolve even without stirring, but it takes time and there is a possibility that local variations in composition will occur.

[0029] The metal chloride alcohol solution used to dissolve the polyamide is preferably a solution produced by separating the polyamide from the metal chloride alcohol solution in which the polyamide is dissolved from the polyamide base fabric. If the concentration or composition has changed during separation and recovery of the polyamide, separation from unnecessary components by extraction, distillation, etc., concentration by distillation, or concentration adjustment by adding metal chloride and / or alcohol may be performed. For example, the metal chloride alcohol solution from which the polyamide has been separated may be concentrated and used in the production method of this embodiment. Since alcohol and metal chloride are not discarded, the environmental load is small, and since the polyamide remaining in the supernatant during separation and recovery of the polyamide can be re-recovered, the recovery rate is improved.

[0030] Each step in the manufacturing method of this embodiment will be described below.

[0031] <Process 1 Melting process> The dissolving step is a step of mixing a mixture containing a urethane-coated polyamide (e.g., a urethane-coated polyamide base fabric) with a metal chloride alcohol solution to dissolve the polyamide. By mixing the mixture with the metal chloride alcohol solution, the polyamide is dissolved from the urethane-coated polyamide in the mixture. In this specification, the solution obtained by mixing the mixture with the alcohol solution of the metal chloride is referred to as a "polyamide solution." The polyamide solution contains dissolved polyamide, urethane that has coated the polyamide, and the like. By separating the coating such as urethane from the polyamide solution, a "solution containing polyamide" can be obtained. The shape of the polyamide base fabric used for dissolution is not particularly limited. Scraps from fabric production or used airbags may be added in their original shape, or may be cut according to the size of the device used for dissolution.

[0032] The temperature at which the mixture and the alcohol solution of the metal chloride are mixed is not particularly limited, but is preferably 30 to 90° C., more preferably 40 to 90° C., and further preferably 40 to 60° C. If the temperature is less than 30° C., dissolution will be slow, and if the temperature exceeds 90° C., the temperature will be higher than the boiling point, which is undesirable from the viewpoints of corrosiveness and decomposition.

[0033] The dissolution may be carried out in either a batch or continuous manner. In the case of a batch type, stirring is not particularly limited, but stirring is preferred, as stirring increases the dissolution rate of the polyamide solid. In the case of a continuous system, the solvent may be continuously passed through the solid, or the solution may be circulated. Circulation is preferred because it allows the amount of solvent used to be reduced.

[0034] The shape of the vessel used in the dissolving step is not particularly limited, and any shape such as a tank type or a circulation type may be used.

[0035] The time for mixing the mixture with the alcohol solution of a metal chloride is not particularly limited, but is preferably 5 minutes to 100 hours.

[0036] The mass ratio of polyamide in the polyamide solution (100 mass%) is preferably 5 to 15 mass%, and more preferably 7 to 13 mass%. If it is less than 5 mass%, too much solvent is required, and if it exceeds 15 mass%, the viscosity increases, prolonging the dissolution time and deteriorating operability. The mass ratio of the polyamide in 100 mass% of the solution containing the polyamide is preferably 5 to 15 mass%, more preferably 7 to 13 mass%. If it is less than 5 mass%, too much solvent is required, and if it exceeds 15 mass%, the viscosity increases, which lengthens the mixing time and deteriorates the operability.

[0037] The viscosity of the polyamide solution at 25° C. is preferably 10 to 20,000 mPa s, more preferably 10 to 10,000 mPa s, and even more preferably 10 to 3,000 mPa s. The higher the viscosity, the higher the polymer concentration, but the polyamide dissolution efficiency decreases due to sticking of the base fabric, etc. The viscosity of the solution containing the polyamide at 25° C. is preferably 10 to 20,000 mPa·s, more preferably 10 to 10,000 mPa·s, and even more preferably 10 to 3,000 mPa·s.

[0038] The method for separating the urethane resin from the polyamide solution is not particularly limited, and examples thereof include a method of scooping up the urethane resin from the solution layer, filtration, centrifugation, sedimentation, etc., and these may be combined. Since fine fragments of the urethane resin may be generated during the dissolution of the polyamide, it is preferable to remove the fine fragments by filtration or a combination of filtration.

[0039] It is preferable to remove other coatings from the polyamide coated with the urethane resin at the same time as removing the urethane resin. The separated urethane resin and other coatings are preferably washed to recover the polyamide-containing solution, since the polyamide-containing solution is attached to them. The washing solvent is not particularly limited, but a calcium chloride methanol solution is preferred. The washing method is not particularly limited, but examples include stirring washing in a tank-type reactor and flow washing in a filter.

[0040] <Polyamide recovery process> The polyamide recovery step is a step of recovering polyamide from the solution containing the polyamide obtained in the dissolving step and from which the urethane resin has been removed. The polyamide may be recovered from the polyamide solution. However, from the viewpoint of further improving the recovery efficiency, it is preferable to recover the polyamide from the solution containing the polyamide after removing any covering material such as urethane resin.

[0041] A method for recovering a polyamide from a solution containing the polyamide includes a method for precipitating the polyamide. The method for precipitating the polyamide from the solution containing the polyamide is not particularly limited, but several precipitation methods are possible depending on the dissolved state of the polyamide. When the polyamide is dissolved by heating, it is possible to precipitate the polyamide by cooling, taking advantage of the temperature dependency of the solubility of the polyamide. In this case, the dissolved polyamide is precipitated from the solution containing the dissolved polyamide without adding an additional solvent to the solution, thereby obtaining a precipitated polyamide.

[0042] In the case where the temperature dependency of the solubility during dissolution is small, the solution containing the polyamide may be mixed with a poor solvent for the polyamide to reduce the solubility and cause precipitation. In this case, a poor solvent is added to the solution containing the dissolved polyamide, and then the dissolved polyamide is precipitated from the solution to obtain the precipitated polyamide. The poor solvent is not particularly limited, but examples thereof include water and alcohols such as ethanol, n-propanol, and isopropanol. The method of adding the poor solvent to the polyamide may be either a method of adding a solution containing the polyamide to the poor solvent, or a method of adding a poor solvent to the solution containing the polyamide, and the addition speed, temperature, stirring speed, etc. during addition are not particularly limited. The amount of poor solvent added is not particularly limited, but is preferably 0.5 to 50 times the mass of the polyamide-containing solution, and more preferably 1 to 10 times the mass. The smaller the amount added, the lower the recovery rate, and the larger the amount added, the larger the amount of solution becomes, requiring more time and energy for treatment.

[0043] When the temperature dependency of the solubility during dissolution is small, the solubility of the polyamide can also be reduced by reducing the concentration of calcium chloride. The method of adding methanol to reduce the concentration of calcium chloride is not particularly limited, but may be either a method of adding a solution containing the polyamide to methanol or a method of adding methanol to a solution containing the polyamide, and the addition speed, temperature, stirring speed, etc. during addition are not particularly limited.

[0044] The shape of the container is not particularly limited, and any shape such as a tank type or a circulation type may be used.

[0045] The precipitated polyamide is preferably recovered by solid-liquid separation. Examples of the solid-liquid separation method include filtration, centrifugation, and sedimentation. Either method may be used in a batch or continuous manner.

[0046] The polyamide obtained by solid-liquid separation is preferably washed with a solvent. The washing liquid is not particularly limited, but for example, a solution having the composition of the liquid portion during precipitation, a good solvent, and a solvent capable of dissolving calcium chloride and the like are used. The additional washing liquid used here is, for example, water, and alcohols such as methanol, ethanol, n-propanol, and isopropanol. The additional washing liquid is preferably methanol. Washing may be performed multiple times as necessary.

[0047] The washing method is not particularly limited, and examples thereof include a batch washing method, a continuous washing method in which a solid is placed in a solid-liquid separation device such as a filter or a centrifugal separator and water is passed through it, and a combination of these methods. After washing, the polyamide can be dried and solidified by distilling off the washing solvent through heating and / or reduced pressure to obtain a powdered polyamide.

[0048] As described above, according to the present embodiment, it is possible to provide a method for producing recycled polyamide with high yield from a mixture in which polyamide, which is useful as an engineering plastic, is coated with urethane.

[0049] <Process for concentrating the metal chloride alcohol solution> The manufacturing method of this embodiment may further include a step of concentrating the metal chloride alcohol solution from the viewpoint of reusing the metal chloride alcohol solution. For example, the metal alcohol solution containing metal chlorides and alcohol obtained in the polyamide recovery step may be concentrated and reused. The concentration method may be, for example, concentration by heating.

[0050] <Recycled Polyamide> The shape of the recycled polyamide produced by the manufacturing method of this embodiment is not particularly limited, and examples include polyamide melted during recycling and formed into pellets, polyamide dissolved in a solvent and then precipitated into a powder, and powder agglomerated to suit handling conditions into tablet form. The above-mentioned recycled polyamide can be used as a raw material for polyamide fibers, polyamide base fabrics, airbags, and the like.

[0051] (Spinning polyamide fibers) The regenerated polyamide fibers can be spun into polyamide fabric. The spinning temperature in melt spinning is preferably 290° C. or higher and 310° C. or lower. Setting the spinning temperature to 310° C. or lower is preferable because thermal decomposition of the polyamide can be suppressed, more preferably 300° C. or lower, and even more preferably 295° C. or lower. On the other hand, a spinning temperature of 290° C. or higher is preferable because the polyamide exhibits sufficient melt fluidity, the discharge amount between the discharge holes is uniform, and high-magnification drawing is possible.

[0052] The shorter the residence time in the melt spinning process (the time from when the polyamide resin is melted until it is discharged from the spinneret), the better. The residence time is preferably 30 minutes or less, more preferably 15 minutes or less, and even more preferably 0.5 minutes to 7 minutes. A short residence time is preferable because cyclopentanones in the polymer increase at the melting temperature.

[0053] For thermal stability in high temperature and high humidity environments, it is preferable to add a copper compound so that the copper concentration relative to the polyamide is 1 to 500 mass ppm, more preferably 30 to 500 mass ppm. By doing so, even if it is left in a high temperature and high humidity environment for a long time or exposed to an environment containing a large amount of ozone for a long time, the deterioration of mechanical performance is extremely effectively suppressed. If the copper content is less than 30 mass ppm, the heat resistance strength retention rate decreases, and if the amount added exceeds 500 mass ppm, the strength decreases.

[0054] The type of copper compound is not particularly limited, and for example, an organic copper salt such as copper acetate, or a copper halide such as cuprous chloride or cupric chloride can be preferably used. The copper compound is more preferably used in combination with a metal halide compound. Examples of the metal halide compound include potassium iodide, potassium bromide, and potassium chloride. The preferred combinations in this embodiment are cuprous iodide and potassium iodide, and copper acetate and potassium iodide. The copper content in the polyamide can be measured by atomic absorption spectrometry, colorimetry, or the like.

[0055] As a stabilizer, organic antioxidants such as hindered phenol antioxidants, sulfur antioxidants, and phosphorus antioxidants, heat stabilizers, light stabilizers such as hindered amines, benzophenones, and imidazoles, and ultraviolet absorbers may be added, although they are not limited thereto. An appropriate amount may be selected, and 1 to 1000 ppm by mass may be added to the polyamide. These additives may be used alone or in combination of several kinds.

[0056] In the melt spinning process, a single-screw or twin-screw extruder is preferably used in the melting section, which can apply an appropriate pressure to the polyamide resin while guiding it to the polymer pipe, gear pump, and spinning pack.

[0057] In addition, it is preferable to filter the polyamide resin using a metal fiber nonwoven fabric filter, sand, or the like before it is discharged from the spinneret, since this stabilizes the spinning operation. The shape of the nozzle holes in the spinneret may be selected according to the cross-sectional shape of the single fibers constituting the filaments to be produced. The yarn spun from the spinneret is solidified with cooling air, a process oil is applied, and the yarn is taken up, stretched, and heat-treated to obtain polyamide fiber.

[0058] The oil agent adhesion rate of the polyamide fiber is preferably 0.5 to 1.5 wt%. If the oil agent adhesion rate is 1.5 wt% or less, the weft yarn hardly has difficulty in flying due to stickiness (tackiness), and the weft yarn transport medium, air or water, does not lose its weft yarn transporting power due to the single yarn bundle being too good compared to the single yarn bundle due to entanglement, resulting in a reduction in apparent cross-sectional area, and weaving stability is good. On the other hand, if the oil agent adhesion rate is 0.5 wt% or more, the weft yarn is smoothly supplied due to the appropriate friction reduction effect, resulting in excellent productivity without weaving stoppage.

[0059] (Polyamide base fabric) In weaving, a water jet loom, an air jet loom, a rapier loom, etc. can be used as the loom. The airbag base fabric is a high-density woven fabric, and it is preferable to manufacture the fabric with good processability by increasing the warp tension in the warping and weaving processes. A high-density woven fabric is formed by setting the warp tension high in weaving and creating effective beating conditions.

[0060] The woven fabric can be subjected to a scouring process to wash off the process oil from the polyamide fibers. The refining step can be performed using hot water or hot compressed water, and the treatment step may be a one-stage treatment or a multi-stage treatment having two or more stages. It is also preferable to perform refining by applying a conventionally known refining agent.

[0061] The woven fabric is preferably heat-set in a heat-setting process. The heat-setting temperature is preferably 110°C or higher and 200°C or lower, and the heat-setting time may be appropriately selected within the range of 0.1 minutes or higher and 30 minutes or lower. In the heat-setting process, the woven fabric is preferably dried under tension so that the shrinkage force of the woven fabric is maintained at a predetermined force. Heat-setting the woven fabric can stabilize the processability of the subsequent resin application process.

[0062] The fabric after the scouring step may be dried as necessary before the heat setting step. The drying temperature is preferably in the range of 80°C to 130°C, more preferably 100°C to 120°C. The treatment time is preferably selected appropriately from 0.1 minutes to 30 minutes. Drying may be performed with the fabric in a relaxed or tensioned state.

[0063] The polyamide base fabric can be used as an uncoated base fabric after being subjected to a heat setting process, but it may also be coated with a coating agent such as silicone or urethane, or heat laminated with a thin film.

[0064] Methods for coating the surface of a woven fabric include immersing the fabric in a resin solution bath, then forming and uniforming the excess resin using a mangle, vacuum, or even a coating knife, bar coating methods such as a comma coater, and spraying the resin using a spray device or a forming device. Of these, the knife coating method is preferred from the viewpoint of applying a small amount of resin uniformly.

[0065] The coating amount is 5g / m 2 More than 100g / m 2 More preferably, it is 10 g / m or less. 2 More than 70g / m 2 The following is more preferably 15g / m 2 More than 30g / m 2 Below is 5g / m 2 The required airtightness can be obtained with an application amount of 100 g / m or more. 2At the following application amounts, the coated fabric has flexibility, good packability, and reduces the overall weight of the bag.

[0066] <Airbag> The airbag may be appropriately selected from among airbags commonly used for the driver's seat, passenger seat, side (including inflatable curtain), rear seat, etc., and the cut shape of the airbag body may be any shape, such as circular, oval, elliptical, rectangular, polygonal, or a combination of these, as long as it satisfies the desired deployed shape. The stitch shape may be a single straight line or multiple parallel straight lines, a zigzag pattern, a combination of straight lines and zigzags, a straight line and a diagonal line, etc. The sewing method may be a commonly used method such as a lock stitch or a double chain stitch, and the stitch pitch may be selected from the range of 20 to 60 times per 10 cm. The sewing thread thickness may be selected from the range of 420d to 3000d, and commercially available sewing threads such as polyamide fiber, polyester fiber, vinylon fiber, aramid fiber, and glass fiber may be used as the thread material. EXAMPLES

[0067] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples.

[0068] The urethane-coated nylon 66 base fabric used in this embodiment (hereinafter, referred to as nylon 66 base fabric) is a base fabric in which 10% of the mass is made of urethane resin.

[0069] [Example 1] 10g of nylon 66 base cloth and 100g of 20wt% calcium chloride methanol solution were added to a 300mL glass bottle containing a stirrer, and the polyamide was dissolved by stirring for 12 hours with a magnetic stirrer while placing it in a water bath at 60℃. The viscosity of the polyamide solution was 500mPa·s. The polyamide solution was passed through a stainless steel mesh with a mesh size of 1mm and a stainless steel mesh with a mesh size of 500μm to remove the urethane resin. The removed urethane resin was returned to the original 1000mL glass bottle, washed with 5g of 20wt% calcium chloride methanol solution, and passed through the mesh again to separate it from the solution containing polyamide. The recovered solution containing polyamide was transferred to a 1000mL beaker, and 500g of methanol was added while stirring. The resulting precipitate was filtered and collected using a 1μm membrane filter. The solid after filtration was thoroughly washed with water. The washed solid was heated and dried in a vacuum dryer at 40℃ to obtain 8.8g of regenerated polyamide (yield 97.8%).

[0070] [Example 2] 7 g of nylon 66 base cloth and 100 g of 10 wt% zinc chloride methanol solution were added to a 300 mL glass bottle containing a stirrer, and the polyamide was dissolved by stirring for 50 hours with a magnetic stirrer while placing it in a water bath at 60 °C. The viscosity of the polyamide solution was 100 mPa s. The polyamide solution was passed through a stainless steel mesh with a mesh size of 1 mm and a stainless steel mesh with a mesh size of 500 μm to remove the urethane resin. The removed urethane resin was returned to the original 1000 mL glass bottle, washed with 5 g of 10 wt% zinc chloride methanol solution, and passed through the mesh again to separate it from the solution containing polyamide. The recovered solution containing polyamide was transferred to a 1000 mL beaker, and 500 g of methanol was added while stirring. The resulting precipitate was filtered and collected using a 1 μm membrane filter. The solid after filtration was thoroughly washed with water. The washed solid was heated and dried in a vacuum dryer at 40 °C to obtain 6.0 g of regenerated polyamide (yield 95.2%).

[0071] [Example 3] In a 300mL glass bottle containing a stirrer, 10g of nylon 6 base fabric (with the same urethane resin content as nylon 66 base fabric) and 100g of 20wt% calcium chloride methanol solution (water content 1000ppm) were added, and the polyamide was dissolved by stirring for 12 hours with a magnetic stirrer while placing it in a water bath at 60℃. The viscosity of the polyamide solution was 400mPa·s. The mixture of polyamide solution and urethane resin was passed through a stainless steel mesh with a mesh size of 1mm and a stainless steel mesh with a mesh size of 500μm to remove the urethane resin. The removed urethane resin was returned to the original 1000mL glass bottle, washed with 20g of 20wt% calcium chloride methanol solution, and separated from the solution containing polyamide by passing it through the mesh again. The recovered solution containing polyamide was transferred to a 1000mL beaker, and 500g of methanol was added while stirring. The resulting precipitate was collected by filtration using a 1μm membrane filter. The solid after filtration was thoroughly washed with water. The washed solid was dried by heating in a vacuum dryer at 40 degrees to obtain 8.5 g of regenerated polyamide (yield 94.4%).

[0072] [Example 4] The filtrate (534 g) obtained in Example 1 was concentrated using an evaporator to obtain 459 g of methanol as a distillate and 75 g of a 20 wt % calcium chloride methanol solution as a bottoms residue. Using the resulting residue, regenerated polyamide was obtained from 7.5 g of nylon 66 base fabric in the same manner as in Example 1, and 6.6 g of regenerated polyamide was obtained (yield 97.8%).

[0073] [Comparative Example 1] 25g of nylon 66 base cloth and 100g of saturated calcium chloride dihydrate methanol solution were added to a 300mL glass bottle containing a stirrer, and the polyamide was dissolved by stirring for 24 hours with a magnetic stirrer while placing it in a water bath at 60°C. The viscosity of the polyamide solution was 35000mPa·s. The polyamide solution was passed through a stainless steel mesh with a mesh size of 1mm and a stainless steel mesh with a mesh size of 500μm to remove the urethane resin. The removed urethane resin was returned to the original 1000mL glass bottle, washed with 20g of saturated calcium chloride dihydrate methanol solution, and passed through the mesh again to separate it from the solution containing polyamide. The recovered solution containing polyamide was transferred to a 1000mL beaker, and 500g of methanol was added while stirring. The resulting precipitate was filtered and collected using a 1μm membrane filter. The solid after filtration was thoroughly washed with water. The washed solid was heated and dried in a vacuum dryer at 40°C to obtain 10.8g of regenerated polyamide (yield 48.0%). When the removed urethane resin was peeled off, it was confirmed that nylon 66 remained in the urethane resin.

Claims

1. A method for producing recycled polyamide using a mixture containing a polyamide coated with a urethane resin as a raw material, comprising: a dissolving step of mixing the mixture with a metal chloride alcohol solution containing a metal chloride and an alcohol to dissolve the polyamide and obtain a polyamide solution, In the dissolving step, the mass ratio of the polyamide in the polyamide solution is 5 to 15 mass%. A method for producing recycled polyamide.

2. A method for producing recycled polyamide using a mixture containing a polyamide coated with a urethane resin as a raw material, comprising: a dissolving step of mixing the mixture with a metal chloride alcohol solution containing a metal chloride and an alcohol to dissolve the polyamide and obtain a polyamide solution, In the dissolving step, the viscosity of the polyamide solution at 25°C is 10 to 20,000 mPa s. A method for producing recycled polyamide.

3. 3. The method according to claim 1, wherein the mixture and the alcohol solution of the metal chloride are mixed at a temperature of 30 to 90° C. in the dissolving step.

4. The method according to claim 1 or 2, wherein the polyamide is an aliphatic polyamide.

5. 3. The method according to claim 1, wherein the metal chloride is zinc chloride or calcium chloride.

6. The method of claim 5, wherein the metal chloride is calcium chloride.

7. The process according to claim 1 or 2, wherein the alcohol is methanol.

8. The method according to claim 1 or 2, wherein the polyamide is nylon 66.

9. 3. The method according to claim 1, wherein the metal chloride alcohol solution is a solution produced by separating polyamide from a metal chloride alcohol solution in which polyamide has been dissolved from a polyamide base fabric.

10. The method according to claim 9, wherein the alcoholic solution of metal chloride is a concentrated solution obtained after separating the polyamide.

Citation Information

Patent Citations

  • Denwakokanhoshiki

    JP1976010704A

  • Apparatus for wiping needle yarn

    JP1983041598A

  • Method for recycling polyamide composition

    JP2018172618A

  • Method for recovering polyamide fibers, method for manufacturing recycled polyamide products, and silicone solution

    JP7024037B1